Recent Progress of RGD Modified Liposomes as Multistage Rocket Against Cancer - Sheikh, Afsana; Alhakamy, Nabil A.; Md, Shadab; Kesharwani, Prashant (Frontiers in Pharmacology, 2022)
Cancer is the most life-threatening disease contributing approximately 9.4 million cancer related death worldwide. Such scenario offers challenge to the scientific researcher to investigate molecules that could act as speed-breaker in the way of cancer. As abiotic drug delivery system, liposome could hold both hydrophilic and lipophilic drug, promote controlled release, accumulate at tumor microenvironment, achieve elongated half-life with enhanced safety profile. To further improve the safety and impair the off-target effect, the surface of liposomes could be modified in a way to be easily identified by cancer cell, promote uptake, and facilitate angiogenesis. Integrins are over expressed on cancer cell, which upon activation promotes downstream cell signaling, which eventually activate specific pathway promoting cell growth, proliferation, and migration. RGD peptide are easily recognized by integrin over expressed cells. Just like a multistage rocket, ligand anchored liposomes can selectively be recognized by target cell, accumulate at the specific site, and lastly release the drug in specific and desired way. This review thus highlighted the role of integrin in cancer development, so to get more insight about the phenomenon of tumor initiation and survival. Since, RGD are recognized by integrin family, the fate of RGD has been demonstrated after its binding with the acceptor’s family and role of RGD based liposomes to target various cancer cells has also been highlighted in the manuscript.